Digital language learning resources: analysis of software features and usage patterns in UK schools - Janjić, Paula; Coventry, Kenny R. (Frontiers in Education, 2025)
The increasing availability of digital technology for second language (L2) learning is transforming traditional teaching methods, yet the quality of these resources remains unclear. A survey was conducted among a stratified sample of second language teachers (N = 118) from UK primary and secondary schools to evaluate the use of digital tools used in classrooms. A rating tool, grounded in educational and language learning theories, was developed to assess individual software features. Results showed extensive use of digital resources, with 89% of teachers utilizing digital devices and over half employing more than three different software types. However, evaluations revealed varying adherence to language learning principles. Strengths were identified in the components of ‘engagement’ and ‘input’, whereas opportunities for improvement are observed in the aspects of ‘output’ and ‘social learning’. Additionally, higher software ratings did not correlate with usage frequency or price. These findings highlight the integration of digital tools in UK language learning pedagogy, but underscore the need for ongoing evaluation to improve software quality and effectiveness.